(untitled) (Medical Forum Monthly, 2024)
Objective: We aimed to study frequency, determinants and obstetrical outcome of unintended pregnancy. Study Design: Cross sectional study Place and Duration of Study: Gynecology and Obstetrics department, during May 2017 to October 2017. Materials and Methods: This study was conducted at the Department of Gynecology and Obstetrics, PUMHS Nawabshah SBA from May to October 2017. Materials and Methods: All pregnant women carrying singleton pregnancy of more than 28 weeks gestation were eligible while women with multiple pregnancy, alcoholics, smokers, and chronic diseases were excluded from the study. Determinants of un-intended pregnancy socio demographic variables as maternal age, educational and economic status, age at marriage, pregnancy related variables as gestational age in weeks, parity, birth interval, booking status, antenatal services and prenatal outcome as preterm birth, low birth weight, stillbirth were recorded. Results: Unintended pregnancy was reported by 47% of women in our study. The following variables shows positive association with unintended pregnancy as maternal aged between 20-40 years, mostly with low education, having more than two births, birth interval less than 12 months, belongs to poor socio economic status, age at marriage less than 20 years, delayed prenatal care, belongs to rural areas while common prenatal outcome observe preterm birth and low birth weight. Conclusion: This study concluded high percentage of unintended pregnancy with substantial negative consequences for women and her child, thus signifying need for effective and directed sex education and family planning facilities.